Information Seeking Behaviour of Four Generation at IPDN Library - Sardi, Auliya Noviyani (Department Library of Governance Institut of Home Affairs, 2022)
Background: The availability of baby boomers, X, millennials, and Gen Z in an organization has become a matter of concern due to the generation gap between these people. This phenomenon can be seen in the Library Unit of IPDN (Institute Government of Home Affairs) as an information provider for students and Academic Community. Purpose: Therefore, this research aimed to describe the information seeking behavior of four generations in IGHA using the Ellis model. Method: It was conducted using a descriptive quantitative method. The population was from the IPDN academic community, totaling 1,776 people, while the sample consisted of 198. Primary and secondary data were obtained from questionnaires and literature, with the instrument developed based on Information Seeking Behavior Model by Ellis. Results: The results showed that all respondents were in an average index (%) of 75% -100%, but those from Gen Z had the highest index (%) for each indicator, namely starting (89%), chaining (90%), browsing (86%), differentiating (90%), monitoring (89%), and extracting (90%). The behavior was in the frequent category and comprised 136, 148, 130, 122, 138, and 142 people in the starting, chaining, browsing, differentiating, monitoring, and extracting groups, respectively. Conclusion: There were differences in information seeking behavior between these four generations. Gen Z is a phydigital and seek unlimited information. Generations X and Y are of working age, with little time to search for information according to the Ellis model. Meanwhile, baby boomers can keep up with technological and information developments. Keywords: Information Seeking Behavior, GAP Generation, Library Services